2021
DOI: 10.1002/jia2.25773
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for HIV virological non‐suppression among adolescents with common mental disorder symptoms in Zimbabwe: a cross‐sectional study

Abstract: Introduction Adolescents are at increased risk of HIV virological non‐suppression compared to adults and younger children. Common mental disorders such as anxiety and depression are a barrier to adherence and virological suppression. The aim of this study was to identify factors associated with virological non‐suppression among adolescents living with HIV (ALWH) in Zimbabwe who had symptoms of common mental disorders. Methods We utilized baseline data from a cluster‐ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Self-reported depression was rare in our cohort (1.5% of all HIVinfected mothers); however, depression was associated with the highest likelihood among all predictors for not achieving VS among women on ART (OR 0.092, corresponding to a 10.8fold higher likelihood of not being virally suppressed). In line with these observations, mental disorders have previously been described as barriers to efficient HIV therapy in Zimbabwean adolescents (51).…”
Section: Self-reported Depressionmentioning
confidence: 53%
See 1 more Smart Citation
“…Self-reported depression was rare in our cohort (1.5% of all HIVinfected mothers); however, depression was associated with the highest likelihood among all predictors for not achieving VS among women on ART (OR 0.092, corresponding to a 10.8fold higher likelihood of not being virally suppressed). In line with these observations, mental disorders have previously been described as barriers to efficient HIV therapy in Zimbabwean adolescents (51).…”
Section: Self-reported Depressionmentioning
confidence: 53%
“…In a South African study of women with a new HIV diagnosis during pregnancy and immediate initiation of ART, disclosure of HIV status to their spouses/intimate partner was associated with a reduced risk of detectable VL >50 copies/ml at delivery (29). Conversely, non-disclosure of HIV status has also been associated with decreased odds for VS in Ugandan pregnant women initiating lifelong ART (57,58) and Zimbabwean adolescents with mental disorders (51). This points to HIV-related stigma as possibly one reason for reduced rates of ART adherence.…”
Section: Non-disclosure Of Hiv Status and Stigmamentioning
confidence: 99%
“…This result was consistent with previous studies, which showed that females were roughly 2.50 times more likely to experience virological failure than males [ 44 , 45 ]. However, other previous studies reported either a higher risk of virological failure in males [ 43 ], or no association between gender and virological failure [ 39 , 42 ]. The inconclusive result on this association needs to be further assessed in large and diverse samples in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…Some previous studies also found that older children had a higher risk of virological failure [ 39 , 40 ], which could be explained by the poorer adherence and higher likelihood of drug resistance in older children [ 39 , 41 ]. Future studies are still needed to further testify this association and verify the reasons between age and virological failure because other previous studies did not detect this association [ 42 , 43 ]. In this study, females were 2.21 times more likely to experience virological failure compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health distress is in turn a key driver of adolescent disengagement with HIV health services, ART non-adherence, unsuppressed viral load and unsafe sex, 28 exacerbated by low levels of disclosure. 29 HIV is a lifelong infection, and there may be particular periods of heightened vulnerability-such as testing, disclosure and transitioning from paediatric into adult HIV care. Emerging evidence suggests that COVID-19 has increased adolescent mental health challenges globally, through interrupting care access 30 and education, 31 and increasing poverty and violence against children.…”
Section: Mental Health and Adolescents Living With Hivmentioning
confidence: 99%